Digital Governance for Sustainable Mobility in Indonesia: Insights from a Bibliometric Analysis of Public Policy and Climate Action - Dyah Kuntorini Dwi Angreni; Ahmad Hidayah; Kamila Dwi Kurniawati (Cakrawala, 2026)
This study aims to map the development, knowledge structure, and research trends of digital governance in relation to sustainable mobility, public policy, and climate action. A bibliometric approach was employed using VOSviewer and R-Bibliometrix. Data were collected through a literature search using the keywords “sustainable mobility”, “governance”, “public policy”, and “Indonesia”. From an initial search of 1,214 publications, 620 publications were selected as the final dataset after screening based on their relevance to sustainability and governance themes. The findings reveal three main research clusters: public service and transparency, digital transformation and performance, and climate change and environmental governance. These clusters indicate that digital technologies, including e-government, big data, and blockchain, not only improve public service efficiency but also strengthen accountability, public participation, and governance capacity in responding to climate-related risks. This study contributes by providing a conceptual mapping of the relationship between digital governance, sustainable mobility, and climate action in Indonesia. Future research should empirically examine how digital technologies are implemented at regional and community levels to support sustainable transportation policies and climate adaptation.